Effect of Washing on the Adhesion of Yersinia enterocolitica on Fish and Shrimp Muscle Surface - Kishore, Pankaj; Suma, D; Minimol, V A; Thakur, Abhishek; Uchoi, Devananda; Nayak, B B (Fishery Technology, 2017)
Water is used traditionally with or without asanitizing agent to wash fresh seafood and to reducepathogens attached to the surface. Ability of Yersiniaenterocolitica to get attached to fish and shrimpmuscle and detached during water washing wasstudied. Dressed tissues were dipped in suspensioncontaining Yersinia enterocolitica 108-109 cells per mland washed sequentially. Bacterial counts andtetrazolium salt reduction were estimated. Thestudy revealed that first wash was more effectivecompared to two subsequent washes. The bacterialreduced from 5.145 log CFU g-1 to 4.445 logCFU g-1 in fish and 5.05 to 3.7 log CFU g-1 in shrimpafter 3 washings. The cells which remained boundafter washing were more active than those which gotwashed and were measured by per cell activity ofthe cells monitored by rate of formazan formed. Thewashing was found to be more effective in removingbacteria in shrimp tissue than in fish tissue providedinitial quality of water was good.